can someone help me out here number 4 plz
![can someone help me out here number 4 plz class=](https://us-static.z-dn.net/files/dce/1b1c12abc2ac1eeae7bedb28a7ca6ada.jpg)
Answer:
(2x + 3)(2x - 1)
Step-by-step explanation:
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 4 × - 3 = - 12, sum = + 4
The factors are + 6 and - 2
Split the middle term using these factors
4x² + 6x - 2x - 3 ( factor the first/second and third/fourth terms )
= 2x(2x + 3) - 1(2x + 3) ← factor out (2x + 3)
= (2x + 3)(2x - 1)